THE ENGLISH â€“ INDONESIAN TRANSLATION ANALYSIS OF FIGURATIVE LANGUAGE IN THE NOVEL â€œTO KILL A MOCKINGBIRDâ€ BY HARPER LEE - Fazny Rahmawati Kilian (Universitas Sarjanawiyata Tamansiswa, 2019)
This research aims to (1) find the kinds of figurative language used To Kill a Mockingbird novel, (2) find out the kinds of translation methods applied by the translator in translating To Kill a Mockingbird novel, and (3) find out the most dominant translation method in translating To Kill a Mockingbird novel. The result of the research shows that there are 294 figurative languages found in the novel based on the types of figurative language that focused on six types namely simile with 20% (70), metaphor 23% (69), hyperbole 21 % (63), personification 20% (59), metonymy 11% (31) and synecdoche 1% (2). This shows that the role of metaphor is dominant than the other figurative languages. Meanwhile, from 294 figurative languages, it was found that there were 3 kinds of translation method out of 8 kinds proposed by Newmark, namely literal, free and communicative translation method. There are 195 literal methods (66%), 58 communicative methods (20%) and 41 free methods (14) were used in translating the figurative language in the novel. Thus, the most dominant translation methods used by the translator is literal method translation.